Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kepuasan Kerja dan Kinerja Karyawan (Studi Kasus PT Bank TabunganPensiunan Nasional,TbkCabang Malang) - Riansari, Titi; Sudiro, Achmad; ., Rofiaty (Jurnal Aplikasi Manajemen, 2012)
xThe objective of the research is to understand the effect of compensation and work environment on work satisfaction and performance. Research population is the employee of Bank BTPN Malang Branchfor 68 people. Inferential Statistic Method is used in the data analysis, by utilizing Generalized Structural Component Analysis (GSCA). In this research, the direct and indirect effects of compensation and work environment on work satisfaction and performance are examined. Result of research indicates that there is a significant direct effect of compensation on work satisfaction. However, a significant direct effect of compensation on employee performance is absent. The employee often considers the wage, salary, and welfare indicators as low. Therefore, the manager is forced to produce a better match between wage, salary and welfare which are given to the employee to improve performance. There was no significant direct effectof work environment on work satisfaction, but there is significant indirect effect of work environment on work satisfaction through employee performance. It seems that the intermediate (intervening) is very necessaryfor the effect of employee performance on work satisfaction. There is a significant reci procal effect of work satisfaction on employee performance.